Association between the cervicovaginal microbiome, BRCA1 mutation status, and risk of ovarian cancer: a case-control study - Nené, Nuno R; Reisel, Daniel; Leimbach, Andreas; Franchi, Dorella; Jones, Allison; Evans, Iona; Knapp, Susanne; Ryan, Andy; Ghazali, Shohreh; Timms, John F; Paprotka, Tobias; Bjørge, Line; et al. (The Lancet. Oncology, 2019)
BACKGROUND: Various factors-including age, family history, inflammation, reproductive factors, and tubal ligation-modulate the risk of ovarian cancer. In this study, our aim was to establish whether women with, or at risk of developing, ovarian cancer have an imbalanced cervicovaginal microbiome. METHODS: We did a case-control study in two sets of women aged 18-87 years in the Czech Republic, Germany, Italy, Norway, and the UK. The ovarian cancer set comprised women with epithelial ovarian cancer and controls (both healthy controls and those diagnosed with benign gynaecological conditions). The BRCA set comprised women with a BRCA1 mutation but without ovarian cancer and controls who were wild type for BRCA1 and BRCA2 (both healthy controls and those with benign gynaecological conditions). Cervicovaginal samples were gathered from all participants with the ThinPrep system and then underwent 16S rRNA gene sequencing. For each sample, we calculated the proportion of lactobacilli species (ie, Lactobacillus crispatus, Lactobacillus iners, Lactobacillus gasseri, and Lactobacillus jensenii), which are essential for the generation of a protective low vaginal pH, in the cervicovaginal microbiota. We grouped samples into those in which lactobacilli accounted for at least 50% of the species present (community type L) and those in which lactobacilli accounted for less than 50% of the species present (community type O). We assessed the adjusted association between BRCA1 status and ovarian cancer status and cervicovaginal microbiota community type, using a logistic regression model with a bias reduction method. FINDINGS: Participants were recruited between Jan 2, 2016, and July 21, 2018. The ovarian cancer set (n=360) comprised 176 women with epithelial ovarian cancer, 115 healthy controls and 69 controls with benign gynaecological conditions. The BRCA set (n=220) included 109 women with BRCA1 mutations, 97 healthy controls wild type for BRCA1 and BRCA2 and 14 controls with a benign gynaecological condition wild type for BRCA1 and BRCA2. On the basis of two-dimensional density plots, receiver-operating characteristic curve analysis, and age thresholds used previously, we divided the cohort into those younger than 50 years and those aged 50 years or older. In the ovarian cancer set, women aged 50 years or older had a higher prevalence of community type O microbiota (81 [61%] of 133 ovarian cancer cases and 84 [59%] of 142 healthy controls) than those younger than 50 years (23 [53%] of 43 cases and 12 [29%] of 42 controls). In the ovarian cancer set, women younger than 50 years with ovarian cancer had a significantly higher prevalence of community type O microbiota than did age-matched controls under a logistic regression model with bias correction (odds ratio [OR] 2·80 [95% CI 1·17-6·94]; p=0·020). In the BRCA set, women with BRCA1 mutations younger than 50 years were also more likely to have community type O microbiota than age-matched controls (OR 2·79 [95% CI 1·25-6·68]; p=0·012), after adjustment for pregnancy (ever). This risk was increased further if more than one first-degree family member was affected by any cancer (OR 5·26 [95% CI 1·83-15·30]; p=0·0022). In both sets, we noted that the younger the participants, the stronger the association between community type O microbiota and ovarian cancer or BRCA1 mutation status (eg, OR for community type O for cases aged <40 years in the ovarian cancer set 7·00 [95% CI 1·27-51·44], p=0·025; OR for community type O for BRCA1 mutation carriers aged <35 years in the BRCA set 4·40 [1·14-24·36], p=0·031). INTERPRETATION: The presence of ovarian cancer, or factors known to affect risk for the disease (ie, age and BRCA1 germline mutations), were significantly associated with having a community type O cervicovaginal microbiota. Whether re-instatement of a community type L microbiome by using, for example, vaginal suppositories containing live lactobacilli, would alter the microbiomial composition higher up in the female genital tract and in the fallopian tubes (the site of origin of high-grade serous ovarian cancer), and whether such changes could translate into a reduced incidence of ovarian cancer, needs to be investigated. FUNDING: EU Horizon 2020 Research and Innovation Programme, EU Horizon 2020 European Research Council Programme, and The Eve Appeal.
Keywords: Cervix Uteri; Humans; Case-Control Studies; cervix uteri; lidé středního věku; studie případů a kontrol; mikrobiota; BRCA1 Protein; Female; rizikové faktory; mladý dospělý; dospělí; nádory vaječníků; Aged; Ovarian Neoplasms; Microbiota; senioři; lidé; Vagina; vagina; Carcinoma, Ovarian Epithelial; Adult; epiteliální ovariální karcinom; ženské pohlaví; Middle Aged; Adolescent; genetická predispozice k nemoci; protein BRCA1; Genetic Predisposition to Disease; Aged, 80 and over; Young Adult; senioři nad 80 let; mladiství; Risk Factors